Immunogenicity, Lot Consistency, and Extended Safety of rVSVΔG-ZEBOV-GP Vaccine: A Phase 3 Randomized, Double-Blind, Placebo-Controlled Study in Healthy Adults. (18th July 2019) - Halperin, Scott A; Das, Rituparna; Onorato, Matthew T; Liu, Kenneth; Martin, Jason; Grant-Klein, Rebecca J; Nichols, Rick; Coller, Beth-Ann; Helmond, Frans A; Simon, Jakub K
Abstract: Background: This double-blind study assessed immunogenicity, lot consistency, and safety of recombinant vesicular stomatitis virus-Zaire Ebola virus envelope glycoprotein vaccine (rVSVΔG-ZEBOV-GP). Methods: Healthy adults (N = 1197) were randomized 2:2:2:2:1 to receive 1 of 3 consistency lots of rVSVΔG-ZEBOV-GP (2 × 10 7 plaque-forming units [pfu]), high-dose 1 × 10 8 pfu, or placebo. Antibody responses pre-/postvaccination (28 days, 6 months; in a subset [n = 566], months 12, 18, and 24) were measured. post hoc analysis of risk factors associated with arthritis following vaccination was performed. Results: ZEBOV-GP enzyme-linked immunosorbent assay (ELISA) geometric mean titers (GMTs) increased postvaccination in all rVSVΔG-ZEBOV-GP groups by 28 days (>58-fold) and persisted through 24 months. The 3 manufacturing lots demonstrated equivalent immunogenicity at 28 days. Neutralizing antibody GMTs increased by 28 days in all rVSVΔG-ZEBOV-GP groups, peaking at 18 months with no decrease through 24 months. At 28 days, ≥94% of vaccine recipients seroresponded (ZEBOV-GP ELISA, ≥2-fold increase, titer ≥200 EU/mL), with responses persisting at 24 months in ≥91%. Female sex and a history of arthritis were identified as potential risk factors for the development of arthritis postvaccination. Conclusions: Immune responses to rVSVΔG-ZEBOV-GP persisted to 24 months. Immunogenicity and safety results support continued rVSVΔG-ZEBOV-GP development. Clinical Trials Registration: NCT02503202. Abstract : Immune responses to rVSVΔG-ZEBOV-GP, measured by ZEBOV-GP immunoglobulin G enzyme-linked immunosorbent assay and plaque reduction neutralization test, were robust and persisted up to 24 months. Together with the favorable safety profile, the immunogenicity results support continued rVSVΔG-ZEBOV-GP development.